2017
DOI: 10.1108/ijphm-09-2016-0047
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the influence of medical representatives and promotional tools on prescribing

Abstract: Purpose The purpose of this paper is to examine reported literature on the influence of medical representatives (MRs) and other promotional tools on drug prescribing behaviour, and to assess whether this effect is different in developed and developing countries. Design/methodology/approach A survey of the literature was conducted across online databases from 2000 to 2016. Eligible studies addressed MRs and other promotion tools used to influence drug prescribing in developed and developing countries. Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 64 publications
(219 reference statements)
0
29
0
Order By: Relevance
“…In the last 10 years, drug brands have evolved into a significant marketing issue 4 , where drug companies often have significant marketing budgets and use the media to create brand awareness among customers . Following this line of research, a brand can create sustainable points of differentiation among competing products . The brand of the drug has long been considered a prominent product feature that influences the prescribing behaviour of physicians .…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 4 more Smart Citations
“…In the last 10 years, drug brands have evolved into a significant marketing issue 4 , where drug companies often have significant marketing budgets and use the media to create brand awareness among customers . Following this line of research, a brand can create sustainable points of differentiation among competing products . The brand of the drug has long been considered a prominent product feature that influences the prescribing behaviour of physicians .…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…suggested that drug brand had a significant and positive effect on prescription behaviour. Furthermore, a recent systemic review of physicians’ perceptions towards branded drugs revealed that brand influences the prescribing behaviour of physicians . Theodorou et al .…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations